2001
DOI: 10.1016/s0031-0182(01)00270-x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital forcing in Pliocene–Pleistocene Mediterranean lacustrine deposits: dominant expression of eccentricity versus precession

Abstract: Milankovitch forcing of climate is expressed in the sedimentary record as lithological cycles that can have one or more of four typical periods related to precession (21 kyr), obliquity (41 kyr) and eccentricity (100 and 400 kyr). In several Mediterranean continental successions, striking differences in the expression of particularly precession and eccentricity appear. We present the results of an additional lower Pliocene lacustrine succession from Lupoaia (southern Romania), and compare the cyclic expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 21 publications
2
27
1
3
Order By: Relevance
“…These results are in agreement with earlier studies in the Mediterranean region and other perimediterranean Neogene records (van Vugt et al, 2001;Abdul Aziz et al, 2003;Abels et al, 2009) which concluded that the 100-kyr and 400-kyr eccentricity minima and maxima were related to periods of low-and high-average precipitation respectively. Since the contribution of the 2.4-Myr cycle to the insolation spectra is very low , it is inferred that long-period orbital forcing is transmitted through modulation of the shorter eccentricity cycles of 400-kyr and (specially) 100-kyr and, consequently, by the amplitude of the precession cycle.…”
Section: Eccentricity Paced Climates In the Circum-mediterranean Areasupporting
confidence: 93%
“…These results are in agreement with earlier studies in the Mediterranean region and other perimediterranean Neogene records (van Vugt et al, 2001;Abdul Aziz et al, 2003;Abels et al, 2009) which concluded that the 100-kyr and 400-kyr eccentricity minima and maxima were related to periods of low-and high-average precipitation respectively. Since the contribution of the 2.4-Myr cycle to the insolation spectra is very low , it is inferred that long-period orbital forcing is transmitted through modulation of the shorter eccentricity cycles of 400-kyr and (specially) 100-kyr and, consequently, by the amplitude of the precession cycle.…”
Section: Eccentricity Paced Climates In the Circum-mediterranean Areasupporting
confidence: 93%
“…Although there are documented astronomically-forced cycles in continental sediments (Agustí et al, 2001;van Vugt et al, 2001;Kruiver et al, 2002;Steenbrink et al, 2006;Amorosi et al, 2008;García-García et al, 2009;Abels et al, 2010), most of them are focused on lacustrine settings with a recording of precessional cycles (e.g. van Vugt et al, 2001) or cyclicity corresponding to changes in obliquity and/or eccentricity (e.g.…”
Section: High-frequency Orbital Forcing?mentioning
confidence: 99%
“…van Vugt et al, 2001) or cyclicity corresponding to changes in obliquity and/or eccentricity (e.g. Steenbrink et al, 2006;Jiménez-Moreno et al, 2013).…”
Section: High-frequency Orbital Forcing?mentioning
confidence: 99%
“…The pebble size in the channels reflects the intensity of runoff which may be controlled by Milankovitch-type climatic cycles. The dominance of the 41 ka obliquity and the precession cycles as found in this region in the Pliocene (Cramp and O'Sullivan, 1999) may also be applicable to the Miocene (e.g., Juhasz et al, 1997;Hilgen et al, 2000;van Vugt et al, 2001). A cyclic variation of precipitation and runoff may be related to an early precursor of the African monsoon, which is dominantly forced by insolation and responds both to the 41 ka obliquity cycle and the 19/23 ka precession cycle (Rossignol-Strick, 1983).…”
Section: Environment and Climatementioning
confidence: 82%